Degradation of Chicken Feathers by Proteus vulgaris And Micrococcus luteus - Lakshmi, T B V (International Journal of Pharmaceutical & Biological Archive, 2013)
Degradation of Chicken Feathers by Proteus vulgaris And Micrococcus luteus